1988
DOI: 10.1007/bf00253447
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative lymphoscintigraphy

Abstract: A radioisotopic method was used to evaluate the state and dynamics of the lymphatic system in 92 patients affected by chronic oedema of the limbs and in 12 control subjects. After interstitial injections of 99mTc-sulphur microcolloid, scans were obtained using a LFOV camera linked to a data processor. The quantitative indices of clearance and lymph node uptake obtained showed good correlation with lymphoedema etiology, controls and ostensibly healthy limbs of patients affected by monolateral disease. In conclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 5 publications
2
52
0
1
Order By: Relevance
“…In this field, few authors rely purely on morphologic data (9,10). The sensitivity of morphologic criteria (7,9,10,12) often appears to be inferior (70%-80%) to that of isolated functional parameters (90% or more) (5,8). In practice, most protocols for examining edemas of the limbs take into account both morphologic data and different functional parameters (6)(7)(8)11,12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this field, few authors rely purely on morphologic data (9,10). The sensitivity of morphologic criteria (7,9,10,12) often appears to be inferior (70%-80%) to that of isolated functional parameters (90% or more) (5,8). In practice, most protocols for examining edemas of the limbs take into account both morphologic data and different functional parameters (6)(7)(8)11,12).…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of morphologic criteria (7,9,10,12) often appears to be inferior (70%-80%) to that of isolated functional parameters (90% or more) (5,8). In practice, most protocols for examining edemas of the limbs take into account both morphologic data and different functional parameters (6)(7)(8)11,12). In fact, our study showed that lymphatic extraction of tracer from the injection site (8,12), or its subsequent nodal accumulation (8), can vary significantly from one examination to the next according to variations in the quantity of tracer injected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em nosso estudo, a análise da curva não possibilitou a distinção entre o membro com e sem linfedema, mesmo após correção pela atividade administrada, o que possivelmente indique a interferência de outros fatores, como a variação na retenção do material em trânsito por cada linfonodo ou por toda a cadeia inguinal. Diversos autores propõem que, ao invés da chegada do radiofármaco na cadeia inguinal, o clareamento do ponto de injeção seria um melhor parâmetro de quantificação [19][20][21][22] .…”
Section: Resultsunclassified
“…In an attempt to gain insight into patterns of regional lymph flow, previous studies have been based on lymphoscintigraphy, using the rate of clearance of a suspension of radiolabelled particles from a subcutaneous depot as a quantitative measure of local lymph flow [4, 5, 6, 7, 8, 9, 10, 11, 12]. The most readily available material for such studies is Tc-99m-nanocolloid.…”
Section: Introductionmentioning
confidence: 99%